English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please help me.

2007-01-27 08:41:17 · 14 answers · asked by Imagine, Its Contagious! 3 in Science & Mathematics Mathematics

In fraction form, please and thank you.

2007-01-27 08:46:41 · update #1

14 answers

6 2/15

If there's 2 sets of 3 1/15, then there would be 6 2/15 in all. You can't simplify it anymore so that's your answer.

2007-01-27 08:44:26 · answer #1 · answered by Anonymous · 0 0

2* 3 1/15 = 2* 46/15 = 92/15 = 6 2/15 .
Choose from the two last expressions

2007-01-27 08:47:04 · answer #2 · answered by santmann2002 7 · 0 0

2/1 x 46/15= 92/15=6 2/15

2007-01-27 11:18:51 · answer #3 · answered by Dave aka Spider Monkey 7 · 0 0

Simple....

2 x 3 = 6
and
2 x 1/15 = 2/15
so your answer is
6 2/15

Normally you would look for common factors in order to simplify the fraction part of your answer, but 2 and 15 don't have any common factors, so it's already in its simplest form.

2007-01-27 08:48:13 · answer #4 · answered by Gonzo 2 · 0 0

92/15 because your doing:
2 times 3 1/15 which is the same as
2 times 46/15
which is equal to 92/15 !

2007-01-27 08:51:35 · answer #5 · answered by smile518 2 · 0 0

92/15

2007-01-27 08:44:19 · answer #6 · answered by Anonymous · 0 0

92/15

2/1 = 46/15 then simplify

2007-01-27 09:06:56 · answer #7 · answered by Red Bear Cries 3 · 0 0

It is 2*46/15 = 92/15. Can't get amy simpler than this.

2007-01-27 08:50:29 · answer #8 · answered by ironduke8159 7 · 0 0

5 and 1/15 is the answer!

2007-01-27 08:45:04 · answer #9 · answered by Pauly W 7 · 0 0

> a million/2(2X+4)-3(X-6)=10 a million/2*2x+4*a million/2-3x-18=10 x+2-3x-18=10 -2x=10+sixteen x=-26/2 x=-13 question #4: 4x^2+10x64 (4x+2)(x+2) question#11 3x+2(3-2y)=0 3y+6-4y=0 -y=-6 y=6 question #sixteen 2 sq. root of sixteen = 4 question # 18: 3y+x=9 3y-4x=-6 sparkling up for x: 3y+x=9 x=9-3y replace x from the equation: 3y-4x=-6 3y-4(9-3y)=-6 3y-36+12y=-6 15y=-6+36 15y=30 y=2 sparkling up for x: replace y from the equation: x=9-3y x=9-3(2) x=9-6 x=3 question # 19: x^2-5x-36=0 (x-9)(x+4)

2016-12-16 15:01:21 · answer #10 · answered by donenfeld 4 · 0 0

fedest.com, questions and answers